Pengaruh E-WOM (Electronic Word of Mouth) di Facebook terhadap Kepuasan Konsumen Dimediasi Keputusan Pembelian pada Markasku - Hamza, Moh.; Adam, Rosida P.; Fadjar, Adfiyani; Wirastuti, Wiri (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2025)
The study aims to analyze the influence of E-WOM (electronic word of mouth) on the facebook social media platform on the level of consumer satisfaction at SMEs Markasku, with purchasing decisions as a mediating variable. Using a quantitative survey approach to 100 active consumers, the data was processed using the structural equation modeling partial least squares (SEM-PLS) method. The results indicate E-WOM significantly and positively influences consumer satisfaction, both directly and through mediation of purchasing decisions. Positive reviews on facebook have been shown to increase consumer trust, influence purchasing decisions, and have an impact on increasing consumer satisfaction. In addition, purchasing decisions strengthen the relationship between E-WOM and consumer satisfaction. This study provides an important contribution to the development of digital marketing literature and offers practical recommendations for SMEs to maximize E-WOM as a strategy to increase consumer satisfaction in the digital era.